Pengaruh Digital Literacy dan Work Ability Terhadap Kinerja Karyawan (Studi Pada PT Buana Fajar Anugrah) - Dunan, Hendri; Jericho, Jericho (Universitas Pahlawan Tuanku Tambusai, 2025)
The aim of this research is to analyze the influence of digital competence and work ability on employee performance at PT Buana Fajar Anugrah. The research method used is a quantitative approach based on a sample of 35 employees. Data collection was carried out through questionnaires using purposive sampling techniques and using a Likert scale. Data processing used validity, reliability, multiple linear regression, and classical assumption tests. The results of the study indicate that: (1) Digital literacy has a positive and significant influence on employee performance with a regression coefficient of 0.448; (2) Work ability has a positive and significant influence on employee performance, with a regression coefficient reaching 0.453; (3) Digital literacy and work ability have a big influence on employee performance with a contribution reaching 67%, while 33% is influenced by other variables that have not been analyzed. This study indicates that increasing digital literacy and work ability can improve employee performance at PT Buana Fajar Anugrah.